In Vitro Antibacterial Activity of Averrhoa bilimbi Leaves Ethanol Extract Against Salmonella typhi - Margaretha Nathania; Eddy Bagus Wasito; Nurina Hasanatuludhhiyah (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Typhoid fever, a major health problem for developing countries, requires alternative therapy to reduce drug resistance.2. A. bilimbi, a native plant of Indonesia, has antibacterial potential, which is effective against S. typhi in vitro. AbstractIntroduction: Some native plants in Indonesia have potential effects on health and medication. This study aimed to determine the potential antibacterial effect of Averrhoa bilimbi (A. bilimbi) leaves ethanol extract against Salmonella typhi (S. typhi) bacteria. Methods: This was an experimental study. The antibacterial potency of A. bilimbi leaves was measured against S. typhi in vitro. Different concentrations of the leaves’ ethanol extract were prepared. The minimum inhibitory concentration (MIC) was evaluated by a macro-dilution method using Mueller Hinton broth. The minimum bactericidal concentration (MBC) value was observed by subculturing the specimen from the previous dilution tube to the nutrient agar.Results: The MIC of A. bilimbi leaves ethanol extract against S. typhi bacteria could not be determined because all the treatment tubes’ colors were dark and turbid. Meanwhile, the MBC value was at 500 mg/ml.Conclusion: A. bilimbi leaves extract had potential bactericidal effects against S. typhi with a MIC value that could not be determined.